Laying performance, genetic parameters, and the expression of FSHβ, LHβ, FSHR, and LHR genes in Japanese quails selected for early egg production - Eman A. Manaa; Mahmoud M. El-Attrouny; Amal EL-Barbary; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Mahmoud S. El-Tarabany; Sherif I. Ramadan (Poultry Science, 2024)
ABSTRACT: Investigating the impact of early egg production selection (the first 90 d of laying) on egg production features, cumulative selection response (CSR), and the mRNA expression of gonadotropins (FSHβ and LHβ), and their receptors (FSHR and LHR), in Japanese quails was the goal. The selection experiment involved 1293 females in all, 257 from the base group and 1036 from the 4 selected generations. Age and body weight at sexual maturity (ASM, BWSM), weight of the first egg (WFE), days to the first 10 eggs (DF10E), egg mass for the first 10 eggs (EMF10E), egg weight (EW), egg number at the first 90 d of laying (EN90D), and egg mass at the first 90 d of laying (EM90D) were all recorded. Most egg production traits had heritability estimates that were low to moderate and ranged from 0.17 to 0.33., where the highest estimates were reported for EN90D (0.33) and BWSM (0.32). With the exception of EN90D, low to moderate positive genetic correlations were observed between ASM and other egg production traits (0.17–0.44). The fourth generation showed significantly (P < 0.05) lower ASM and DF10E but higher BWSM, WFE, EN90D, EM10E, and EM90D when compared with the base generation. CSR were significant (P < 0.05) for ASM (−6.67 d), BWSM (27.13 g), WFE (0.93 g), DF10E (−1.25 d), EN90D (7.24 egg), EM10E (10.57 g), and EM90D (140.0 g). FSHβ, LHβ, FSHR, and LHR gene mRNA expression was considerably (P < 0.05) greater in the fourth generation compared to the base generation. In conclusion, selection programs depending on the efficiency of egg production (EN90D) could improve the genetic gain of egg production traits and upregulate the mRNA expression of FSHβ, LHβ, FSHR, and LHR genes in selected quails (fourth generation). These findings might help to enhance breeding plans and create commercial lines of high egg production Japanese quails.